2016
DOI: 10.1111/radm.12198
|View full text |Cite
|
Sign up to set email alerts
|

Technological impact of R&D grants on utility models

Abstract: We evaluate the impact of public grants on the technological output of Spanish manufacturing companies using the utility models as a measure and compare them with patents. We postulate that capabilities of the firm play a decisive moderating role in the relationship between grants and utility models. Results suggest that a firm's capability to constantly maintain an updated knowledge base has a positive influence on the abovementioned relationship. Also, firm's capabilities of planning innovation, and cooperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…I n industries with fast-changing technologies, strategic alliances are primary in product innovation (Visnjic et al, 2016), value creation and competitive advantage (Gomes et al, 2011;Torres-Barreto et al, 2016). Collaborative product innovation strategies and R&D cross-fertilisation (Faems et al, 2005;Cloodt et al, 2006;Colombo and Rabbiosi, 2014) enable firms to modify or develop new products to meet continuously changing customer needs and preferences (Utterback and Abernathy, 1975;Krzeminska and Eckert, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…I n industries with fast-changing technologies, strategic alliances are primary in product innovation (Visnjic et al, 2016), value creation and competitive advantage (Gomes et al, 2011;Torres-Barreto et al, 2016). Collaborative product innovation strategies and R&D cross-fertilisation (Faems et al, 2005;Cloodt et al, 2006;Colombo and Rabbiosi, 2014) enable firms to modify or develop new products to meet continuously changing customer needs and preferences (Utterback and Abernathy, 1975;Krzeminska and Eckert, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Beneito (2006) [34]) analysed how patents and UMs are associated with internal and external R&D. She assumed that patents and UMs approximate significant and incremental innovations, respectively, and found using panel data of Spanish manufacturing firms that significant innovations (patents) are mainly developed in-house, whereas contracted R&D is more orientated towards incremental innovations (UMs). Torres-Barreto et al (2016) [35] analysed the association between R&D grants and UMs in Spain and reported that regional and national R&D grants do not have a significant direct effect on obtaining UMs. Based on Korean firm-level data, Kim et al (2012) [22] reported that UM innovations contribute to firm growth and innovation when firms are technologically lagging, but they contribute insignificantly when firms are technologically more advanced.…”
Section: Choices and Motives To Use Umsmentioning
confidence: 99%